Developing a high-strength Al-Mg-Si-Sc-Zr alloy for selective laser melting: Crack-inhibiting and multiple strengthening mechanisms. (July 2020) - Li, Ruidi; Wang, Minbo; Li, Zhiming; Cao, Peng; Yuan, Tiechui; Zhu, Hongbin
Abstract: To develop high-strength Al alloys for selective laser melting (SLM) additive manufacturing, we designed a series of Al-Mg(-Si)-Sc-Zr alloys and additively manufactured them using atomized alloy powders. In the absence of Si, the developed Al-xMg-0.2Sc-0.1Zr ( x = 1.5, 3.0 and 6.0 wt%) alloys are all susceptible to hot cracking and the average crack density increases with increasing Mg content. The addition of 1.3 wt% Si into the Al-6Mg-0.2Sc-0.1Zr alloys effectively inhibits hot cracking during SLM and simultaneously refines the microstructure, and thus leading to enhanced mechanical properties in the as-printed samples. By further fine-tuning the alloy compositions, we designed a new alloy Al-8.0Mg-1.3Si-0.5Mn-0.5Sc-0.3Zr. This new alloy demonstrates significantly refined microstructure consisting of submicron cells with coherent Al3 (Sc, Zr) nano-particle (2–15 nm) residing in the cell and intergranular Al-Mg2 Si eutectic (Mg2 Si diameter 10–100 nm). High-density stacking faults and a unique 9R phase are formed in the as-printed sample. The tensile strength and elongation of the as-printed sample are up to 497 MPa and 11%, respectively. After the aging treatment, the tensile strength reaches 550 MPa, while the ductility ranges from 8% to 17%, depending on the aging conditions. In addition to solid solution strengthening, grain boundary strengthening and nanoparticle strengthening, the high-density stacking faults also contributes to strengthening. Graphical abstract: Image, graphical abstract